Classification of Vascular Anomalies: An Update - Steiner, Jack E.; Drolet, Beth A. (Seminars in Interventional Radiology, 2017)
Vascular anomalies present both a diagnostic and therapeutic challenge to physicians. Identification of these lesions is difficult due to their immense phenotypic variability, and naming conventions for vascular anomalies have historically been inconsistent. Terms such as “hemangioma” are informative when used correctly, but can cause confusion and miscommunication if applied indiscriminately to all vascular anomalies. Accuracy in classification is essential, as both disease course and therapeutic options differ greatly depending on the particular vascular anomaly present. In order for clinicians to properly diagnose and treat patients with these diseases, a unified nomenclature must be employed. This section provides an update on the current classification of vascular anomalies, with clinical descriptions of the most commonly encountered lesions, and clarifies the ambiguous nomenclature present in the existing literature.
Keywords: vascular anomalies; malformation; hemangioma; classification; interventional radiology